Social Media as a Channel to Promote Youth Participation in Governance - Suhaimi, Safiah; Abıdın, Nor Azizah Zainal; Yeon, Asmah Laili (South Asian Journal of Social Sciences and Humanities, 2020)
Youth is the largest group in the structure of society in Malaysia. Youth is a valuable national asset and generation to be proud of. Youth is an experience that can shape the level of dependence of an individual, which can be marked according to different cultural perspectives in different ways. When social participation is used today, participation in governance will be rapid. The problem happened when lack of social media sharing channels for the continued engagement of young people. The youth believed that they still lacked the social media platforms needed for effective participation and expressed little confidence in their involvement. This paper analysed social media potential as channels for youth governance participation. The methods that used an extensive literature search which is secondary data. The social media is also critical for youth engagement in governance as knowledge channels. The Social Media and Participation literature review will be reviewed. Drawing on the final findings, social media plays an important role in youth engagement thus highlighting all the functions of social media.